Optimal control study to enhance oil production in labscale Vapex by varying solvent injection pressure with time. (1st June 2015) - Muhamad, Hameed; Upreti, Simant R.; Lohi, Ali; Doan, Huu
Summary: In this study, we determine and validate optimal policies of solvent injection pressure versus time to enhance oil production in labscale Vapex or vapor extraction of heavy oil. The study utilizes propane as solvent for a heavy oil of viscosity 14 500 mPa s. The necessary conditions for maximum oil production are derived using a detailed mass transfer model with interfacial solvent concentration versus time as a control function. Based on these conditions, a computational algorithm is developed and implemented to determine the optimal control, which is then converted into the optimal policy of solvent injection pressure versus time using experimental data. The experiments demonstrate that the optimal policy enhances oil production by 20–37% compared with that using constant solvent injection pressure. Moreover, the average deviation of the optimally calculated oil production from its experimental counterpart, both obtained using the same optimal solvent injection policy, is found to be a low value of 4.8%. Copyright © 2015 John Wiley & Sons, Ltd.